Social Services Disrupted: Changes, Challenges and Policy Implications for Europe in Times of Austerity - Anneli Anttonen (New Horizons in Social Policy series, 2017)
Public social services are a key component of the welfare state in most of Europe, although their development trajectories, coverage and legal status still vary considerably among countries. How such services are provided, and for whom, impacts significantly on social and territorial cohesion, gender balance and, ultimately, on the development of any society. However, while much is discussed and written about social policy and welfare systems, social services remain somewhat neglected. Although they have gained a stronger foothold in national legislations and social policy agendas, their status remains weaker compared to education or health. Moreover, because of the austerity measures following the 2008 financial crisis, they have been subject to cuts and reorganisation, which have brought about significant disruption. This book revives the discussion on public social services and their redesign, with a focus on services relating to care and the social inclusion of vulnerable groups. Conveying the main findings of the EU-funded COST Action IS1102 Social Services, Welfare States and Places, the book provides rich information on the changes that occurred in the organisation and supply of public social services over the last thirty years in different European places and service fields. Despite the persisting variety in social service models, three shared trends emerge: public sector disengagement, 'vertical re-scaling' of authority and 'horizontal re-mix' in the supply system. The consequences of such changes are evaluated from different perspectives - governance, social and territorial cohesion, labour market, gender - and are eventually deemed 'disruptive' in both economic and social terms. The policy implications of the restructuring are also explored. The book will appeal to a broad audience: researchers and students, policy-makers, civil servants, service providers, social workers and users' organisations.